Parental Approaches to Reading to 0- to 7-Year-Old Children: Choices, Experiences and Impact - Teodora Genova; Nadezhda Gadzhakova; Sabina Eftimova (Педагогически форум)
The study presents a part of the results of a study of parental approaches to reading to children ages 0 to 7 years, with an emphasis on how parents make their choices and overlay their personal experiences on the reading process. The research examines factors such as frequency of reading, choice of literary works, parent-child interaction during reading, and the influence of parental experience on children's preferences. The survey revealed that parents regularly read to their children for a period of 10 to 20 minutes, preferring fairy tales and adventure stories with rich illustrations. Reading plays an essential role in family life as a tool for learning and developing the imagination. The findings highlight the importance of reading for children's psychological well-being and offer directions for future improvements in parenting approaches in this area.